Some Determinants of Compensation Decisions - Freedman, Sara M. (Academy of Management Journal, 1978)
This research investigated the effects of three variables upon compensation decisions. Results indicated that, in a simulated personnel task, both subordinate pay equity and subordinate equity off the job directly affected subjects' decisions. The strength of the subordinate's demand for a raise also influenced compensation decisions through its interaction with each of the other two variables.